MONITORING OF MECHANICAL SUGARCANE HARVESTING THROUGH CONTROL CHARTS - Voltarelli, Murilo A. [UNESP]; Silva, Rouverson P. da [UNESP]; Zerbato, Cristiano [UNESP]; Paixao, Carla S. S.; Tavares, Tiago de O. [UNESP] (Soc Brasil Engenharia Agricola, 2015)
Statistical process control in mechanized farming is a new way to assess operation quality. In this sense, we aimed to compare three statistical process control tools applied to losses in sugarcane mechanical harvesting to determine the best control chart template for this quality indicator. Losses were daily monitored in farms located within Triangulo Mineiro region, in Minas Gerais state, Brazil. They were carried over a period of 70 days in the 2014 harvest. At the end of the evaluation period, 194 samples were collected in total for each type of loss. The control charts used were individual values chart, moving average and exponentially weighted moving average. The quality indicators assessed during sugarcane harvest were the following loss types: full grinding wheel, stumps, fixed piece, whole cane, chips, loose piece and total losses. The control chart of individual values is the best option for monitoring losses in sugarcane mechanical harvesting, as it is of easier result interpretation, in comparison to the others.
Keywords: quality; agricultural mechanization; moving average; EWMA